Parametrization of generalized Heisenberg groups - Teerapong Suksumran (2020)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. Let M be a left module over a ring R with identity and let β be a skew-symmetric R-bilinear form on M. The generalized Heisenberg group consists of the set M× M× R= { (x, y, t) : x, y∈ M, t∈ R} with group law (x1,y1,t1)(x2,y2,t2)=(x1+x2,y1+y2,t1+β(x1,y2)+t2).Under the assumption of 2 being a unit in R, we prove that the generalized Heisenberg group decomposes into a product of its subset and subgroup, similar to the well-known polar decomposition in linear algebra. This leads to a parametrization of the generalized Heisenberg group that resembles a parametrization of the Lorentz transformation group by relative velocities and space rotations.